Wizerunek kobiety w kronice Mistrza Wincentego - Malinowska, Jolanta (Acta Universitatis Lodziensis. Folia Historica, 1999)
The article concerns three aspects of Medieval woman: as a ruler, as mother and as ruler’s adviser (meaning person from a close circle of a ruler). All characters who appeard in Master Wincenty’s Chronicle were evidently positive or negative. Woman regarded as positive should be perfect both as a ruler and as mother, even when it did not agree with historical sources known to the author. On the other hand, woman regarded as negative should be bad mother as well as an incompetent ruler or woman having harmful influence on her husband. Semiramis – queen of Assyria, Tamyris - queen of Skythai, Rycheza - wife of Mieszko II and Helena - wife of Kazimierz Sprawiedliwy are the most throughly described women of the Chronicle. They were showed both as rulers and mothers.